An overview of worldwide and regional time trends in total mercury levels in human blood and breast milk from 1966 to 2015 and their associations with health effects. (April 2019) - Sharma, Brij Mohan; Sáňka, Ondřej; Kalina, Jiří; Scheringer, Martin
Abstract: Background: Mercury is a pollutant of global concern. To protect human health and environment from mercury pollution, the Minamata Convention on mercury entered into force in 2017. Objectives: To support a future effectiveness evaluation of the convention, this study assesses worldwide and regional time trends of total mercury levels in human blood and breast milk across different population sub-groups in the last half-century prior to entry-into-force of the Minamata Convention. This study also provides an overview of the epidemiological literature showing evidence of associations between mercury exposure (in terms of total mercury levels in whole blood, cord blood, and breast milk) and human health. Methods: We searched electronic databases to identify articles published prior to June 14, 2017 and reported total mercury levels in any of three biological matrices (whole blood, cord blood, or breast milk) and/or associations with human health. Temporal trends of total mercury levels in the selected biological matrices across different population sub-groups were estimated using a linear fit of the log-transformed data. In parallel, statistical methods were employed to assess any possible effect of sources of inhomogeneity (i.e. study and population characteristics such as age, sex, ethnicity, source of exposure, sampling period, and geographical region) in the collected studies. Furthermore, a summary of significant and relevant associations between mercury exposure and human health conditions in children and adults was prepared. Findings: We found significant declines in total mercury levels in whole blood, cord blood, and breast milk between 1966 and 2015. A regional overview of total mercury levels in whole blood, cord blood, and breast milk suggests the highest levels in South America, followed by Africa or Asia whereas the population groups from Europe or North America displayed the lowest levels of total mercury in the selected biological matrices. We observed conclusive consistent associations of mercury exposure with selected health conditions, especially neurodevelopment and neurotoxicity in children and adults. For several other health conditions, reported findings in the collected studies do not support conclusive associations. We also found that several studies demonstrated significant associations between mercury exposure below the USEPA reference level and various health conditions. Conclusions: This study provides a worldwide and regional overview of trends in total mercury levels in human blood and breast milk and associated health risks prior to entry-into-force of the Minamata Convention and calls for further epidemiological investigations from across the globe to fully understand the health implications of mercury exposure. Highlights: Mercury (Hg) exposure overview prior to the Minamata Convention is provided. Total Hg levels in blood and breast milk have significantly declined since 1960s. Total Hg blood and breast milk levels were found the highest in South America. Health effects of Hg exposure were conclusive only for certain health conditions. Further epidemiological studies are needed to comprehend health effects of Hg.